CERMINAN KETANGGUHAN USAHA MIKRO KECIL MENENGAH: SEBUAH STUDI KASUS BISNIS KELUARGA DI INDONESIA - Stevi Jimry Poluan; Rizka Fatkhin Nisa; Sari Wijayanti; Muhammad Husni Tamrin (Among Makarti)
Abstract : Family businesses are one of the businesses that strengthen the economy of a country and globally because they provide opportunities for others to work and get paid for living. Micro, small and medium enterprises (MSMEs) are family businesses that are commonly found in Indonesia. In addition, it often experiences prolonged internal problems that become complicated. This research uses a case study of UMKM X in Salatiga, which experienced problems for twenty years but was able to survive and rise. This research uses an exploratory approach, namely a qualitative method by deepening the problems that occur through in-depth interviews with three main resource persons. The research found that the way these MSMEs solve problems or internal conflicts so that they rise and get better. In addition, conflict management needs to be supported by leadership and governance so that managing conflicts becomes more efficient.